THE ANALYSIS OF TEMPERATURE AND SHRINKAGE-RHEOLOGICAL STRESS IN TWO-DIMENSIONAL SYSTEMS WITH AN EXTERNAL CERAMIC-METAL LAYER - Stadnychenko, Vyacheslav (Proceedings of National Aviation University (archive), 2006)
In the work the temperature and shrinkage-rheological stresses in friction surfaces with ceramic-metal layer that is obtained at using of tryboretrofitting mixes are researched. The results presented by authors allow to improve mathematical models of stress-deformation condition of ceramic-metal system available on today.